Complexes of gold(I) with a chiral diphosphine and bis(pyridine) ligands: Isomeric macrocycles and a polymer. (14th December 2016) - Wheaton, Craig A.; Puddephatt, Richard J.
Graphical abstract: The self-assembly of gold(I) with both binap (PP) and bis(amidopyridyl) (NN) ligands has given either homochiral or heterochiral macrocyclic or polymeric complexes. Abstract: The self-assembly of [Au2 (μ-(±)binap)X2 ], which have weakly coordinated anions X −  = trifluoroacetate, triflate or nitrate, with bis(amidopyridyl) ligands (NN) has given three different macrocyclic complexes of general formula [Au4 (μ-(±)binap)2 (μ-NN)2 ]X4, an open complex [Au2 (μ-(±)binap)(κ 1 -NN)2 ]X2, and a polymer [{Au2 (μ-(±)binap)(μ-NN)} n ]X2 n . Macrocycles with both homochiral ( RR / SS ) and heterochiral ( RS / SR ) combinations of the two binap ligands in the cations [Au4 (μ-binap)2 (μ-NN)2 ] 4+ have been structurally characterized. The polymeric complex has the syndiotactic (heterochiral) architecture. The donor ability of the anion X − is shown to affect both the degree of self-assembly in solution, through competition with the bis(amidopyridyl) ligand for coordination to gold(I), and the conformation of the bis(amidopyridyl) ligand in the products, through hydrogen bonding effects. In solution, there is a rapid equilibrium between cyclic and open chain oligomers, as determined by ESI-MS and NMR studies.